Field trials of the Biassed Heterodyne Method of Exploration for Sulphide Minerals. Issue 1 (1st December 2018) - White, Robert; Collins, Steve; Leslie, Keith; Oertel, Alan; Sloot, Andrew
Abstract : Theoretical investigation and laboratory testing indicate that it may be possible to detect buried sulphide deposits by utilising non-linearity of electrical conduction between semi-conducting sulphide grains. In these tests, the method of detection of the non-linear conductivity effects relies on the heterodyne principle whereby two frequencies will mix to give intermodulation sum and difference frequencies in the presence of non-linear conduction. Field tests of the method were run over known mineralisation at the Kempfield deposits 180km west of Sydney. Two modified Induced Polarisation transmitters were used in a gradient array configuration. Signals were detected using custom built receivers incorporating both 24-bit and 31-bit analog-to-digital converters. Significant logistical problems were encountered due to a number of factors including interference from one transmitter on another and possible interference in the receiver circuitry. The transmitter to transmitter interference precluded trialling the use of a DC bias to emphasise any non-linear mixing terms. Evidence of the interference between transmitters highlighted the need for careful checking that the intermodulation effects are not arising within the electronic circuitry rather than from the earth. The data gathered in the field trial is confusing in that it has obvious problems with signals that are not related to the desired effects. However, when approximate corrections for these are made, a pattern emerges that is correlated with the known sulphide distribution and Induced Polarisation responses. It appears that the heterodyne method has detected sulphide mineralisation at Kempfield but there are many obstacles to overcome before this can routinely be used for exploration.